THE POETIC IMAGE OF COLLECTION OF POEMS OF MOAYED TAYEB “BLING DAMMA BRSEDBEEN “ - ABDULLAH HAJI, DR. NOZAD (Journal of Duhok University, 2019)
This research is an attempt to analyze the artistic image of the poems included in the poetic collection of the poet Muayad Tayeb Bling Damma Brsedbeen “.  It is certain that the subject of this research is now an important and exciting area in the literary criticism due to the fact that this subject is an important literary genre and a major component of time in poetry .What we see in this poetic collection is the poet's attempt to embody many themes, meanings and references, both directly and indirectly in this literary genre. This research is an attempt to enrich the library of Kurdish literary criticism, specifically in the field of applicationIn this research, the researcher explained the subject of the poetic art image in terms of concept, definition, importance and its genres in theoretical way and then the researcher worked on the analysis of these species   in a practical way to the contents of those texts poeticIn conclusion, the researcher reached the results of the most important is that all the images in these poetic texts is a direct expression of the suffering and tragedies of the Kurdish nation in addition to the existence of a large range of live scenes and constant, which embodies the struggle of the Kurdish people